DEVELOPING ASSESSMENT FOR SPEAKING - Yenny Rahmawati; Ertin Ertin (IJEE (Indonesian Journal of English Education), 2014)
Recently there have been debates on assessing students’ performances on speaking since the cultural and subjective issues embedded in bringing awareness on how teachers construct their speaking assessment. The main focus of this paper is a way to design assessment for speaking suitable for the Indonesian context at a university level. This paper stresses the criteria of effective assessment proposed by Brown and Abeywicrama which consists of a specific criterion, an appropriate task, a maximum output and practical and a reliable scoring procedure. It is recommended that teachers develop their speaking assessment which is appropriate and contextual.